Sosialisasi Pemanfaatan Tanaman Serai sebagai Obat Anti Nyamuk untuk Pencegahan Penyakit DBD kepada Masyarakat Desa Cabak Kec. Tlogowunggu Kabupaten Pati - Wildayanti Wildayanti; Aprillia Puspitasari Tunggadewi; Mera Putri Pratitis; Yulia Pratiwi; Luthfiana Nurulin Nafi’ah; Gunawan Firmansyah; Yanulia Handayani; Rochim Rochim; Yustisia Permatasari; Diah A’inurrahmawati (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
Community Service Activities (PKM) occurred in Cabak Village, Tloguwunggu District, Pati Regency. This PKM activity aims to provide socialization about the benefits of lemongrass plants as medicine for preventing dengue fever. Participants in this PKM activity are the people of Cabak Village, Tlogowungu District, Pati Regency. This socialization activity began by providing material on the use of lemongrass plants as medicine including efficacious substances, pharmacological benefits in medicinal plants, and how to process lemongrass plants that are productive as anti-mosquitoes with the help of media in the form of leaflets and brochures to facilitate the delivery of information to the community. This activity was welcomed positively by the Cabak Village Community as seen from the feedback during the Q&A session. The results of the socialization can be seen from the increase in knowledge about how to use lemongrass plants as anti-mosquito drugs to prevent dengue fever.